Inclusion of students coming to Poland from abroad - Bożena Marzec; Michał Borda (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
While analyzing the teaching and attitudes of Pope Francis, we decided to devote this article to the issue of inclusion. Considering the sphere of our interests – education, broadly understood – we focused on the inclusion of students coming from abroad, in the education system in Poland. In our publication, we rely on legal regulations, the results of research and control carried out by the Supreme Audit Office in the field of education of children of foreigners and Polish citizens returning to the country, studies by  researchers of the above-mentioned issues, and we discuss a case study. The conclusions are clear: there are more and more students coming from abroad into Polish schools; despite declarations, schools are not fully prepared for their admission when all responsibility for the organization of education rests with school principals and teachers. The role of pedagogical supervision in this respect is insufficient. It is worth paying special attention to practical guidelines for teachers in order to effectively implement the pedagogy of inclusion.